Herman Miller : classic furniture and system designs for the working environment. - Berry, John R., ....- (London : Thames and Hudson, 2005)
In 1936, Herman Miller Inc. founder D. J. De Pree committed Herman Miller to "modern" furniture. The rest is history: their continuing collaboration with some of the giants of modern design has made Herman Miller synonymous with quality in design. Herman Miller examines the company's powerful contributions by looking at the problems that design can solve and how creative thinking can benefit the world. Aside from having produced icons of modern furniture, Herman Miller has revolutionized office systems and furniture in the workplace. A definitive history of design and the company's work since its founding, Herman Miller features the legendary designs of Charles and Ray Eames, George Nelson, Isamu Noguchi, Gilbert Rohde, Bill Stumpf, Don Chadwick, and many more. It is a must-read for collectors, designers, professionals, students, and anyone with an interest in design. In 1936, Herman Miller Inc. founder D. J. De Pree committed Herman Miller to "modern" furniture. The rest is history: their continuing collaboration with some of the giants of modern design has made Herman Miller synonymous with quality in design. Herman Miller examines the company's powerful contributions by looking at the problems that design can solve and how creative thinking can benefit the world. Aside from having produced icons of modern furniture, Herman Miller has revolutionized office systems and furniture in the workplace. A definitive history of design and the company's work since its founding, Herman Miller features the legendary designs of Charles and Ray Eames, George Nelson, Isamu Noguchi, Gilbert Rohde, Bill Stumpf, Don Chadwick, and many more. It is a must-read for collectors, designers, professionals, students, and anyone with an interest in design.